Extracellular secretion of cloned aerolysin and phospholipase by Aeromonas salmonicida. - Wong, K R (1989)
The promoterless structural genes for aerolysin and the extracellular phospholipase of Aeromonas hydrophila were inserted into a multi-host-range expression vector and transferred into Aeromonas salmonicida and Escherichia coli. In both species, gene expression was under the control of the inducible tac promoter of the vector. Neither the phospholipase nor the aerolysin was released by intact E. coli. Instead, both proteins accumulated in the periplasm, leading to reduced growth and eventual cell death. When the aerolysin gene inserted into the vector contained its own promoter, the toxin was expressed constitutively by A. salmonicida but not by E. coli. Production of aerolysin and the phospholipase by A. salmonicida did not affect cell growth, and the proteins were correctly processed and exported by intact cells. Both proteins could also be detected in the periplasm, where their concentrations were considerably higher then they were outside the cells. Periplasmic aerolysin was rapidly released when cells were transferred to fresh medium, indicating that this compartment is part of the normal export pathway and that the protein is not shunted there as a consequence of overproduction. Plasmid-coded aerolysin did not appear to compete with the cell proteins for export components, as even when very large quantities of aerolysin were being exported by A. salmonicida, there was no effect on chromosomal protease release and only a modest reduction in the export of chromosomal phospholipase.